1991
DOI: 10.2176/nmc.31.162
|View full text |Cite
|
Sign up to set email alerts
|

Extravasation from Anterior Choroidal Artery in a Child with Moyamoya Disease

Abstract: A rare association of moyamoya disease with intra and periventricular hemorrhage in an 8-year-old girl is presented. Angiography showed that the cause of hemorrhage was extravasation from the dilated anterior choroidal artery. Ventriculoperitoneal shunt and encephalomyosynangiosis have prevented clinical or neurological deficits for over 6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, hemorrhage of a dilated AChA can even occur in children. For instance, in 1991, Kameyama et al reported an 8-year-old girl who presented bilateral intraventricular hemorrhage from a dilated AChA 55 . In addition, an aneurysm could develop from an outpouching of the vessel wall in some fragile portions of the artery that function in maintaining prominent collateral circulation 56 .…”
Section: Moyamoya Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…However, hemorrhage of a dilated AChA can even occur in children. For instance, in 1991, Kameyama et al reported an 8-year-old girl who presented bilateral intraventricular hemorrhage from a dilated AChA 55 . In addition, an aneurysm could develop from an outpouching of the vessel wall in some fragile portions of the artery that function in maintaining prominent collateral circulation 56 .…”
Section: Moyamoya Diseasementioning
confidence: 99%
“…An encephaloduroarteriosynangiosis was performed to decrease the hemodynamic overload on the AChA, and the follow-up procedure successfully induced the regression of all the weak points 53 . Furthermore, Kameyama et al reported an 8-year-old girl with an intraventricular hemorrhage from the dilated AChA who received a ventriculoperitoneal shunt, and an encephalomyosynangiosis prevented recurrent bleeding for over 6 years 55 .…”
Section: Moyamoya Diseasementioning
confidence: 99%